Vox dei, Vox demonium: A Cursory Exploration of “Sound Thinking” in Horror Film - Wallin, Jason (Théologiques)

(untitled) (Faculté de théologie et de sciences des religions, Université de Montréal, 2018)
Vox dei, vox demonium marks a cursory attempt to consider a kind of “sound thinking” largely singular to horror film. The essay focuses in particular on the status of “metaphysical subjectivity” as it is modulated by the “sound thinking” of such horror films as The Exorcist, The Amityville Horror, and The Exorcism of Emily Rose, amongst others dealing specifically with audio conceptualizations of demonic possession and invocation.